Nanotechnology platforms for cancer, and beyond - Ferrari, Mauro (Henry Stewart Talks, 2015)
Nanoplatforms for triple-negative breast cancer, Nanotextured surfaces (NanoTraps) for early diagnostics & therapeutic monitoring, MultiStage Vectors (MSV) & Transport Oncophysics for treatment of metastatic cancer, Nanofluidic drug delivery implants (nDS), Regenerative medicine: BioNanoScaffolds (BNS) for post-traumatic osteoregeneration